A Meta-Analysis of Risk Factors for Transient and Permanent Hypocalcemia After Total Thyroidectomy - Qin, Yuan; Sun, Wei; Wang, Zhihong; Dong, Wenwu; He, Liang; Zhang, Ting; Zhang, Hao (Frontiers in Oncology, 2021)
Abstract Background: As hypocalcemia is the most common complication of total thyroidectomy, identifying its risk factors should guide prevention and management. The purpose of this study was to determine the risk factors for postthyroidectomy hypocalcemia. Methods: We searched PubMed, Web of Science and EMBASE through January 31, 2019, and assessed study quality using the Newcastle–Ottawa Scale. Results: Fifty studies with 22,940 patients met the inclusion criteria, of which 24.92% (5716/22,940) had transient hypocalcemia and 1.96% (232/11,808) had permanent hypocalcemia. Significant (P < 0.05) predictors of transient hypocalcemia were: younger age, female, parathyroid autotransplantation (PA), inadvertent parathyroid excision (IPE), Graves’ disease (GD), thyroid cancer, central lymph node dissection, preoperative severe Vitamin D deficiency, preoperative Vitamin D deficiency and a lower postoperative 24 h parathyroid hormone (PTH) level. Preoperative magnesium, preoperative PTH and Hashimoto's thyroiditis were not significant predictors of transient hypocalcemia. IPE, GD and thyroid cancer were associated with an increased rate of permanent hypocalcemia, but gender and PA did not predict permanent hypocalcemia. Conclusion: Important risk factors for transient and permanent hypocalcemia were identified. However, given the limited sample size and heterogeneity of this meta-analysis, further studies are required to confirm our preliminary findings.